Panama : 2009 Article IV Consultation; Staff Report; Staff Statement and Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Panama. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
Strong economic fundamentals helped Panama contain the adverse impact of the global economic downturn and financial turmoil. The 2009 Article IV Consultation highlights that real GDP of Panama in 2008 grew by 9.2 percent. Panama's large banking system has weathered the global financial crisis relatively well. Executive Directors have noted that Panama is facing the global economic crisis from a position of strength. Directors have also commended the authorities for the fiscal consolidation of recent years and the associated rapid decline in the public debt-to-GDP ratio.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet